2023
DOI: 10.1002/ldr.4599
|View full text |Cite
|
Sign up to set email alerts
|

Biochar affects the distribution of phosphorus in the soil profile by changing the capacity of soil to adsorb phosphorus and its distribution within soil macroaggregates

Abstract: A large number of studies suggested that biochar can affect the adsorption of phosphorus (P) in soil and the distribution of P in soil aggregates, but it is still unclear whether biochar can indirectly affect the distribution of P in soil profiles through the influence of these two factors. Therefore, the ability of maize straw biochar to mitigate the risk of loss of P and improve the distribution of P in soil profile was evaluated by studying the capacity of soil to adsorb P from the soil and distribution fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…There were differences in the effects of BC on soil nutrients, with some studies showing that N fertilizer and BC combination increased the available soil P and K contents [ 40 , 41 ], which was also confirmed by the present study. What is more, Liu et al [ 42 ] found that BC altered the distribution of available P in 0–20 cm soil by increasing the adsorbing capacity of P in soil. In the present study, BC application increased the available P in all soil profiles by nearly 2-fold of that in the N420 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There were differences in the effects of BC on soil nutrients, with some studies showing that N fertilizer and BC combination increased the available soil P and K contents [ 40 , 41 ], which was also confirmed by the present study. What is more, Liu et al [ 42 ] found that BC altered the distribution of available P in 0–20 cm soil by increasing the adsorbing capacity of P in soil. In the present study, BC application increased the available P in all soil profiles by nearly 2-fold of that in the N420 treatment.…”
Section: Discussionmentioning
confidence: 99%